Analytical Study of Teak Provenance Tests in North Raipur Division of Maohya Pradesh - Suri, S. K. (Indian Forester, 1984)
Forest tree improvement programmes start wilh the study of available variation in the entire range of species distribution and delimitation of population capable of providing the best tree. This is done by the provenances tests. In North Raipur Division of Madhya Pradesh teak plantations were raised from the seeds obtained from Maharashtra (Kanara origin). Burma Kerala (Nilambur) Madhya Pradesh (Betul and Tenduchus) and Karnataka (Kakankoti) and sample plots were laid out in 1938 as a part of the All India Teak Seed Origin Co-oprrative Experiment. Quantitative and qualitative analysis of the growlh performances of these provenances has been presented in this paper. The indication are that teak seed origin of Nilambur is the most suitable and adaptable In Ihis tract.